Geo-mapping Periwayatan Hadis Dari Kalangan Perempuan - Rofiatul Ubaidillah; Said Kurnia Ramdhani (FIQHUL HADITS : Jurnal Kajian Hadits dan Hukum Islam, 2023)
The tradition of transmitting hadith is dominated by men rather than women, there were 132 female narrators during the Companion period, which is equal to 12.6% of all hadith transmitters. Meanwhile, after Thabaqat Sahabat, there was a drastic decline in female hadith transmitters, namely 30 narrators. As a result, women's role construction is considered unequal to men's from a gender perspective. By mapping the narration of hadith from women centered in 4 cities, namely Medina, Basrah, Kufa and Syam. So researchers will reveal how culture, ethnicity and subordination influence the tradition of narrating hadith. This type of research uses library research, data is obtained through searching primary and secondary literature related to the mapping of hadith narration from women in the book oficles tis'ah. The results of this research show that the lack of hadith transmission from women is influenced by a holistic understanding and complex interactions between humans and the environment, which can provide the basis for a more inclusive approach and involving a gender perspective in human geography. This research has implications for feminism in gender positions and the important role of female hadith transmitters.